Self-assembled 3D-microstructured dual carbon black filled polymer nanocomposite-coated fabric for tunable electromagnetic interference shielding. Issue 2 (1st February 2023) - Sarkar, Kajal; Khanra, Sipra; Sharma, Sujit; Ghorai, Sanjoy Kumar; Chattopadhyay, Santanu
Abstract: Dual carbon black (CB) was used to create self-assembled three-dimensional (3D)-microstructured polymer nanocomposite by a simple solution mixing process. A mechanical stirrer was employed for uniform dispersion and minimizing CB aggregates sizes in the viscous blended medium of hydrolyzed polyvinyl alcohol (PVA) and natural rubber latex (NRL). A stable 3D-microstructural architecture was obtained when an extremely high volume fraction (0.54) of dual CB was used. 3D-microstructured polymer nanocomposite was then applied on the cotton fabric and characterized for the final performance of electromagnetic interference (EMI) shielding effectiveness. The morphological and microstructural analysis revealed that dual CB at a particular ratio of 10:90 (smaller:larger) could provide excellent electrical conductivity (>1.5 S/cm) as well as EMI shielding when assessed against a frequency range of 8.2–12.4 GHz. A durable ultra-thin layer (100 µm) of nanocomposite was sufficient to achieve tunable >31 dB shielding effectiveness.